Transesterifikasi Minyak Ikan Perak (Mene maculata) Dengan Katalis CaO Dari Cangkang Telur Ayam - Tahya, Kartika; Tahya, Candra Yulius; Kainama, Healthy (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2019)
Silver fish (Mene maculata) is a type of pelagic fish found in the Moluccas sea, this fish has a high oil content so that it is easy to extract the oil content for transesterification. The transesterification reaction of oil from silver fish oil needs a catalyst, and heterogenous catalyst is a better choice. This study was determined the fatty acid methyl ester composition of M. maculata by transesterification process using heterogeneous CaO catalyst from chicken egg shells through 3 steps i.e. oil isolation, CaO catalyst synthesis, and oil transesterification reactions. Oil isolation was carried out by soxhletation method using petroleum ether with the oil content was 13.51%. Synthesis of CaO catalyst was carried out by calcination at 1000 Â°C for 2 hours and then charactererized by XRD. Fish oil is transesterified using CaO catalyst in a ratio of 11% (w/v) of the mixture. Furthermore, fatty acid methyl esters obtained were analyzed using GC-MS. The results showed 6 methyl ester fatty acids as composition of transesterification products which were methyl myristic (11.85%), methyl palmitoleate (8.71%), methyl palmitic (25.13%), methyl oleic (9.49%), methyl stearic (10.04%), and methyl 5,8,11,14-eikosatetraenoate (1.96%).